(untitled) (International Journal of Engineering and Computer Science, 2017)
This The process of estimating the geographical location of sensor nodes, called localization is an important research area in WSN. Accurate localization or tracking of wireless device is a crucial requirement for many emerging location aware systems. Fields of application include search & research, medical care, intelligent transportation, location based billing, security, home automation, industrial monitoring and control, location-assisted gaming, and social networking. This work attempts to deal with Classical Multidimensional Scaling (CMDS) technique to estimate the mapping of nodes. Further mapping is done with Neural network (NN) to further improve the accuracy of estimated node position. Comparison results show improved localization with NN implementation.